Wszyscy byli przemytnikami. Obraz przestępczości przemytniczej i dewizowej w latach 1956–1970 - Madej, Krzysztof (Pamięć i Sprawiedliwość, 2008)
The current work discusses the range and types of smuggling and foreign currency speculation in communist Poland of the 1960s. Special attention was paid to the economic and legal conditions of this form of crime and subjective aspects. The author has paid special attention to the fact that, in the contemporary political and economic reality, customs and foreign currency speculation was (outlandish though it may sound) rather exclusive, due to the continued closure of Poland’s borders. Moreover, regional conditions of this form of crime are mentioned, depicting the social and historical differences of Poland of the time. It should be underlined that apart from the growth of this kind of crime in large cities and port towns, there were special circumstances in Upper Silesia and Pomerania. In the 1960s, some inhabitants of these areas were receiving pensions from the FRG, in contradiction to foreign currency regulations then in force. The description of the aforementioned situation is enriched by an analysis of the ‘Zalew’ affair, treated as a case study, in which offi cers of the Security Service and Citizens’ Militia were involved in smuggling and foreign currency speculation, mainly on the route between Warsaw and West Berlin. This example also presents the way in which mechanisms the authorities employed against economic crimes were degenerating and themselves becoming the source of criminal activities. They were especially favored by uncontrolled, broad operational activities and informal relations between offi cers and their secret agents.